Clinical and Translational Evidence for BALIMONT, a Lactobacillus acidophilus-Centered Biotic Composition, in Modulating Immune-Inflammatory Responses - Ziraoui, Anas; Khan, Zara; Valenti, Rico (Scientific Journal of Technology, 2026)
Background: Low-grade inflammation, mucosal-barrier disruption, and recurrent gastrointestinal inflammatory symptoms frequently coexist in adults with immune-inflammatory dysregulation. Multi-strain probiotic systems and postbiotic preparations have both shown anti-inflammatory potential in human studies, but formulation-specific evidence remains essential. Objective: We aimed to present a evidence paper for the BALIMONT composition by integrating retained formulation benchmark data with available clinical trials and meta-analyses relevant to its strains, postbiotic strategy, biomarker framework, and symptom targets. Methods: We retained the original composition architecture, comparator logic, core numerical benchmarks, and three source figures from the development dossier. We then searched peer-reviewed public sources up to March 2026 for randomized controlled trials, placebo-controlled trials, pilot studies, and meta-analyses involving Lactobacillus acidophilus, Lactiplantibacillus plantarum, Bifidobacterium longum, probiotics, postbiotics, inflammatory biomarkers, and gastrointestinal symptom outcomes. We prioritized adult human data and outcome measures directly relevant to hs-CRP/CRP, IL-6, TNF-alpha, IL-10, calprotectin, and GI symptom burden. Results: The retained BALIMONT benchmark program showed a stronger comparator-direction signal for inflammatory suppression and barrier support than the live-bacteria-only reference, including a 68.2% reduction in total serum inflammatory factors and a 42.6% increase in colonic tight-junction protein expression in the lead example, versus 32.5% and 18.3%, respectively, in the comparator framework. Across external human evidence, a meta-analysis of 42 randomized trials reported significant reductions in hs-CRP, TNF-alpha, and IL-6 together with higher IL-10 after probiotic supplementation, while a 2023 umbrella meta-analysis also supported reductions in CRP, TNF-alpha, and IL-6. Strain-relevant clinical studies further showed improvements in bloating with Lactobacillus acidophilus NCFM plus Bifidobacterium lactis Bi-07, decreased inflammatory and lipid-related markers with heat-killed Lactiplantibacillus plantarum L-137 in overweight adults, improved IBS-D symptom severity with both live and heat-treated Bifidobacterium longum CECT 7347, and significant reduction in fecal calprotectin with Lactiplantibacillus plantarum HEAL9 in older adults with chronic low-grade inflammation. Conclusions: The currently available human evidence supports the anti-inflammatory plausibility of the BALIMONT design and aligns with its retained benchmark endpoints, particularly for CRP-related inflammation, cytokine modulation, GI symptom improvement, and postbiotic-enabled translational relevance. A prospective registered trial remains necessary for direct confirmation of this exact formulation.